A grounded theory study on leader authority formation process in China. Issue 3 (1st August 2016) - Zhang, Xiao-feng; Zhang, Xiao-juan; Li, Lei; Li, Gui-quan; Xi, You-min
Abstract : Purpose: This study focused on the authority formation process of Chinese enterprise leaders, with the purpose of finding out how an ordinary newly-established firm leader develops into a real top leader and achieves the status of legitimacy in a well-known enterprise. Design/methodology/approach: Based on constructivist grounded theory, this paper investigates the formation mechanism of entrepreneurial authority in China by employing the rich data of Liu Chuan-zhi's leader activities. Findings: 1. In the 'evolution' path of authority formation, leaders continually consolidate and improve their authority through two classes of exceptional management activities: 'emergency rescue' and 'promotion activities'. The successful realization of exceptional management activities benefits from a leaders' management experience accumulation and relationship maintenance with the government. 2. In the 'design' path of authority formation, leaders consolidate and improve their authority by exercising their position of power. Leaders' legitimacy is reflected by making strategic decision and demonstrating discretion of position power. Additionally, passing on an inspiring leaders' thoughts and ideas to an organization's members is accomplished through the construction of organization culture, institutionalization and convention. Research limitations/implications: First, our findings are based on only Liu Chuan-zhi's case. We still need more cases to compare and develop our findings and seek theoretical saturation in a broader sense. Second, our qualitative analysis is based on secondary data and future research could consider the introduction of interviews, video and other types of research data. Originality/value: Under the parallel paths which are 'evolution' and 'design', the dynamic leader authority formation model in China is founded.